Disentangling Speaking Barriers Faced by Sports Students in Classroom Discussion: A Case Study in Indonesian EFL Classroom - Arief Styo Nugroho; Obay Jambari; Puji Siswanto; Ima Mukhofilah (Universitas Majalengka, 2022)
Speaking skills learned by EFL learners in their class often left some unsolved problems until the end of the term. Such kinds of conditions affect the learning achievement of the students on one hand. On the other hand, the problems are still there and have never been solved. Therefore, the present study scrutinized the students' speaking barrier faced by the sports student department in a classroom discussion at one of the private higher education in Indonesia. In this study, twenty-four students voluntarily participated as participants, and five of them were then interviewed to get comprehensive data. The questionnaire was used to capture students' attitudes and barriers to dealing with linguistic knowledge they face in classroom discussions. The items of the questionnaire are comprised of 17 items with Likert-type items ranging from "strongly agree" to "strongly disagree", semi-structured interviews were also administered in collecting the data needed for this study. Then, the quantitative data got were analyzed using SPSS version 20 for Windows and the percentage are made. While the qualitative data were analyzed qualitatively using content analysis. The speaking barriers are identified and appraisals were then made by the researchers. From the data analysis, the study reveals that the speaking barriers are classified into three categories inter alia: linguistic barriers, material barriers, and psychological barriers.